ANRIL Promoter DNA Methylation: A Perinatal Marker for Later Adiposity - Lillycrop, K.; Murray, R.; Cheong, C.; Teh, A.; Clarke-Harris, R.; Barton, S.; Costello, P.; Garratt, E.; Cook, E.; Titcombe, P.; Shunmuganathan, B.; Liew, S.; et al. (2016)
© 2017 The Authors. Experimental studies show a substantial contribution of early life environment to obesity risk through epigenetic processes. We examined inter-individual DNA methylation differences in human birth tissues associated with child's adiposity. We identified a novel association between the level of CpG methylation at birth within the promoter of the long non-coding RNA ANRIL (encoded at CDKN2A) and childhood adiposity at age 6-years. An association between ANRIL methylation and adiposity was also observed in three additional populations; in birth tissues from ethnically diverse neonates, in peripheral blood from adolescents, and in adipose tissue from adults. Additionally, CpG methylation was associated with ANRIL expression in vivo, and CpG mutagenesis in vitro inhibited ANRIL promoter activity. Furthermore, CpG methylation enhanced binding to an Estrogen Response Element within the ANRIL promoter. Our findings demonstrate that perinatal methylation at loci relevant to gene function may be a robust marker of later adiposity, providing substantial support for epigenetic processes in mediating long-term consequences of early life environment on human health.